Dulaang salamisim - Montero, Trisha Allysse Acelar (2014)
"This undergraduate production thesis focuses on changing what the society imposes on out liberty of choice. We set aside our feelings for they become a routine. We conform to the standards set by the majority and due to the routines established, we settle for less than what we deserve. We just let things happen."